EFFECT OF “PANAROOT-98” ON THE CLINICAL AND PHYSIOLOGICAL CONDITION OF OSTRICH - Shakhlo Aliyevna, Babaeva (International Journal on Orange Technologies, 2022)
The article describes the effectiveness and influence of the drug "Panaroot-98" on the clinical and physiological indicators of 3 month-old ostriches: development, weight gain.